Serum interleukin-6 as a biomarker of disease activity and severity in chronic spontaneous urticaria: a case control study in urban south Indian population - Suresha, Nikhil Ram Jonna; Yadalla, Hari Kishan Kumar; Shivappa, Naveen (International Journal of Research in Dermatology, 2025)
Background: Chronic spontaneous urticaria (CSU) is a challenging dermatological condition marked by recurrent wheals lasting over six weeks without identifiable triggers. While its pathogenesis is not fully understood, emerging evidence suggests a role for pro-inflammatory cytokines, particularly interleukin-6 (IL-6), in disease activity. However, its relevance as a biomarker for disease severity remains to be clarified. To evaluate serum IL-6 levels in CSU patients and determine their correlation with disease severity, compared to healthy controls. Methods: A case-control study was conducted in the Department of Dermatology at Raja Rajeswari Medical College and Hospital from April 2023 to September 2024. Fifty CSU patients and fifty age- and sex-matched healthy controls were enrolled. Disease severity was assessed using the Urticaria Activity Score over 7 days (UAS7). Serum IL-6 levels were measured using ELISA. All calculations were performed using Statistical Package for the Social Sciences (SPSS) version 20 (SPSS Inc., Chicago). Results: Most CSU patients (66%) were young adults (20–40 years), with equal gender distribution. Severe disease (UAS7: 16–42) was observed in 72% of patients. Mean IL-6 levels were significantly higher in CSU patients than in controls (9.1±5.1 vs. 3.12±2.8 pg/ml, p=0.004). IL-6 levels showed a significant positive correlation with disease severity. Conclusions: Serum IL-6 is significantly elevated in CSU patients and correlates with disease severity. It may serve as a promising biomarker for monitoring disease activity and tailoring treatment in CSU, warranting further investigation into its therapeutic potential.